MEMBUMIKAN PESAN DAMAI AL-QUR’AN (AS-SALÁM) SEBAGAI MEDIATOR KOMUNIKASI BANGSA - Egi Tanadi Taufik; Dzalfa Farida Humaira (An-Nida : Jurnal Komunikasi Islam, 2020)
Various conflict transformation through shows that the message of peace has entered a transitional phase that is quite prospective in the Indonesian Islamic societies. On the other hand, the phenomenon of the "Presidential Candidate Election for 2019-2024’s period" since August 4th ago was feared to break the harmony being built between groups in Indonesia because of the symptoms of religious commercialization. To secure the adaptation and maturity of the peace transition in this phase, a comprehensive approach for the message of peace in the Qur'an (AsSalám) is needed as the national communication media. This article is expected to be able to provide new ideas to reassure the phase of conflict transformation that is currently occurs in Indonesia, as well as being a strong fortress that will stem the onslaught of commercialization of religion. Berbagai konflik sosial keagamaan transformasional melalui menunjukkan bahwa konsep damai telah memasuki fase transisi religiusitas yang cukup prospektif di tengah masyarakat Islam Indonesia. Di sisi lain, demam “Pemilihan Calon Presiden Periode 2019- 2024” Agustus 2019 lalu dikhawatirkan memecah kembali keharmonisan yang sedang dibangun di antara golongan-golongan di Indonesia karena gejala komersialisasi agama. Untuk mengamankan adaptasi dan kematangan transisi perdamaian pada fase tersebut, diperlukan pendekatan yang komprehensif antar umat Islam Indonesia dengan pesan perdamaian dalam Al-Qur’an (As-Salám) sebagai media komunikasi berkebangsaan. Artikel ini diharapkan mampu memberikan gagasan baru untuk “menyejukkan” fase transformasi konflik yang tengah bergolak di Indonesia, serta menjadi benteng kokoh yang akan membendung serangan komersialisasi agama.